PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI REJOSARI TAHUN AJARAN 2013/2014 - riyanto, fajar (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Contextual Teaching and Learning (CTL) Approach in Improving Social Science Learning of The Fourth Grade Students of SDN Rejosari in The Academic Year of 2013/2014. This research aims to: describe the implementation steps of CTL, improve social science learning, explain problems and solutions of CTL approach. This research was implemented in three cycles. Data sources were students, peers, and documents. Data collection techniques applied observation, interviews, tests, and documentation. Validity of data used triangulation of source and triangulation of techniques. Data analysis applied qualitative and quantitative analysis. Results from this research showed the learning process in the first cycle 71,75%, second cycle 75,98%, and third cycle 80,04%. The results of students in activities pretest to 7,69%, the first cycle 32,69%, the second cycle 50 %, and the third cycle 90,39%.Keywords: Contextual Teaching and Learning (CTL), social science learning. Abstrak: Penerapan Pendekatan Contextual Teaching and Learning (CTL) dalam  Peningkatan Pembelajaran IPS Siswa Kelas IV SD Negeri  Rejosari Tahun Ajaran 2013/2014. Penelitian ini bertujuan: mendeskripsikan langkah-langkah CTL, meningkatkan pembelajaran IPS, serta menjelaskan kendala dan solusi pendekatan CTL. Penelitian dilaksanakan dalam tiga siklus. Sumber datanya adalah siswa, teman sejawat dan dokumen. Teknik pengumpulan data menggunakan observasi, wawancara, tes, dan dokumentasi. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data menggunakan analisis kualitatif dan kuantitatif. Hasil dari penelitian ini menunjukkan proses belajar pada siklus I 71,75%, siklus II 75,98%, dan siklus III 80,04%. Ketuntasan hasil belajar pada kegiatan pretes 7,69%, pada siklus I 32,69%, siklus II 50%, dan siklus III 90,39%. Kata kunci: Contextual Teaching and Learning (CTL), pembelajaran IPS.